Neurobiological Underpinnings of the Projection of Conscious Contents - Pereira, Alfredo [UNESP] (Imprint Academic, 2023)
The projection of conscious content is a central feature of Max Velmans’ theory of consciousness, implying that conscious experiences are built within a conversation of minds and worlds in which they form a ‘reflexive’ unity – as stated in his reflexive monism theory. What are the neurobiological structures and functions that underpin the experience of conscious contents being located in a spatio-temporal frame outside the nervous system that instantiates them? In this paper I offer informed speculation about these neuro-biological structures on the basis of the concept of projection within the psychophysical ‘egocentric space’, having the central nervous system at the origin of coordinates and the interface with the environment as the horizon. The reasoning is based on the work of several neuroscientists on feedback signals from the motor to sensory neuron systems, building a picture of how they support the projective process. I also call attention to the integrative role of glial cells in the generation of localized sensations and other conscious contents.